2018
DOI: 10.18632/oncotarget.25253
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the type of dietary protein on the development of ovarian cancer

Abstract: We evaluated whether different dietary protein qualities (isocaloric diets involving animal (casein) or plant protein (soy protein) could inhibit the ovarian cancer growth in mice and improve their prognosis and whether chemotherapy had different tumor reducing effects on these mice. In the mice of the 20% plant protein group, the ovarian cancer growth at 5 weeks after tumor implantation was clearly reduced in comparison to the mice in the 20% animal protein group (p< 0.001). The serum levels of insulin and IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…26 Structural proteins like meat and fish proteins are less efficient in elevating the insulin and IGF-1 plasma concentrations than milk proteins. 27,28 Milk contains leucine, glutamine, palmitate that promote more than others the activation of mTORC1 (serine and threonine protein kinase that regulates cell growth, proliferation, motility and survival, synthesis protein, and transcription). 29,30 3.9% of the milk composition is also characterized by fats, 98% of which by triglycerides, (approximately 65% of the total is made up of saturated fatty acids, mainly represented by palmitic acid which accounts for approximately 30% by weight of the total fatty acids, myristic acid and stearic acid.…”
Section: Nutrition In Cancer Carementioning
confidence: 99%
“…26 Structural proteins like meat and fish proteins are less efficient in elevating the insulin and IGF-1 plasma concentrations than milk proteins. 27,28 Milk contains leucine, glutamine, palmitate that promote more than others the activation of mTORC1 (serine and threonine protein kinase that regulates cell growth, proliferation, motility and survival, synthesis protein, and transcription). 29,30 3.9% of the milk composition is also characterized by fats, 98% of which by triglycerides, (approximately 65% of the total is made up of saturated fatty acids, mainly represented by palmitic acid which accounts for approximately 30% by weight of the total fatty acids, myristic acid and stearic acid.…”
Section: Nutrition In Cancer Carementioning
confidence: 99%
“…High-grade serous carcinoma reflects the classic clinical picture of ovarian cancer that is highly sensitive to anticancer drugs. More than 90% of cases have TP53 mutations, and about half are thought to originate from the fallopian tube [9,10]. On the other hand, low-grade serous carcinoma is thought to occur in the background of serous borderline malignant tumors, with few cases of advanced disease; however, proliferative activity and anticancer drug sensitivity are low.…”
Section: Appendices I Serous Carcinomamentioning
confidence: 99%
“…On the other hand, low-grade serous carcinoma is thought to occur in the background of serous borderline malignant tumors, with few cases of advanced disease; however, proliferative activity and anticancer drug sensitivity are low. Low-grade serous carcinoma has been reported to have many cases with KRAS and BRAF somatic mutations [9,10]. Although the estrogen receptor is positive, the effectiveness of hormonal therapy has not been verified in clinical studies [9,10].…”
Section: Appendices I Serous Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…In another population-based case-control study in the USA, an increased whole milk consumption and the intake of lactose was associated with a higher risk of developing ovarian cancer (highest quartile vs. lowest: OR = 1.97 p = 0.008). Using mouse models, our group evaluated whether different dietary protein qualities involving animal (casein: extracted from milk) or plant protein (soy protein) could inhibit ovarian cancer growth [130]. We found that the PI3K/AKT/mTOR pathway, a downstream signaling pathway of IGF-1, was more strongly activated by the intake of animal protein (casein) than the intake of plant protein (soy protein) in mice with ovarian cancer.…”
Section: Ovarian Cancermentioning
confidence: 99%